The emergence of biotechnology : - Orsenigo, Luigi (Pinter, 1989)
"The Emergence of Biotechnology" examines the early stages of the evolution of biotechnology explaining how technological change proceeds in modern industrial economies. It focuses upon the process of creation and modification of institutions in a wide definition which organized and supported the innovative activities of a variety of different agents in conditions of uncertainty. The patterns of evolution in biotechnology in the USA, Japan, UK, Germany and France are compared, analyzing the different systems of innovation and their different technological capabilities and institutional set-ups. Within each country the main actors are identified as the scientific system, the company sector and government and the interaction between these is examined closely. In conclusion, the author considers future prospects and new possibilities for the biotechnology industry.